Incorporating sensitive cardiac substructure sparing into radiation therapy planning. Issue 11 (18th October 2020) - Morris, Eric D.; Aldridge, Kate; Ghanem, Ahmed I.; Zhu, Simeng; Glide‐Hurst, Carri K.
Abstract: Purpose: Rising evidence suggests that cardiac substructures are highly radiosensitive. However, they are not routinely considered in treatment planning as they are not readily visualized on treatment planning CTs (TPCTs). This work integrated the soft tissue contrast provided by low‐field MRIs acquired on an MR‐linac via image registration to further enable cardiac substructure sparing on TPCTs. Methods: Sixteen upper thoracic patients treated at various breathing states (7 end‐exhalation, 7 end‐inhalation, 2 free‐breathing) on a 0.35T MR‐linac were retrospectively evaluated. A hybrid MR/CT atlas and a deep learning three‐dimensional (3D) U‐Net propagated 13 substructures to TPCTs. Radiation oncologists revised contours using registered MRIs. Clinical treatment plans were re‐optimized and evaluated for beam arrangement modifications to reduce substructure doses. Dosimetric assessment included mean and maximum (0.03cc) dose, left ventricular volume receiving 5Gy (LV‐V5), and other clinical endpoints. As metrics of plan complexity, total MU and treatment time were evaluated between approaches. Results: Cardiac sparing plans reduced the mean heart dose (mean reduction 0.7 ± 0.6, range 0.1 to 2.5 Gy). Re‐optimized plans reduced left anterior descending artery (LADA) mean and LADA0.03cc (0.0–63.9% and 0.0 to 17.3 Gy, respectively). LV0.03cc was reduced by >1.5 Gy for 10 patients while 6 cases had large reductions (>7%) in LV‐V5. Left atrial mean dose was equivalent/reduced in all sparing plans (mean reduction 0.9 ± 1.2 Gy). The left main coronary artery was better spared in all cases for mean dose and D0.03cc . One patient exhibited >10 Gy reduction in D0.03cc to four substructures. There was no statistical difference in treatment time and MU, or clinical endpoints to the planning target volume, lung, esophagus, or spinal cord after re‐optimization. Four patients benefited from new beam arrangements, leading to further dose reductions. Conclusions: By introducing 0.35T MRIs acquired on an MR‐linac to verify cardiac substructure segmentations for CT‐based treatment planning, an opportunity was presented for more effective sparing with limited increase in plan complexity. Validation in a larger cohort with appropriate margins offers potential to reduce radiation‐related cardiotoxicities.